2022
DOI: 10.3390/molecules27123844
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Molecular Basis for the Better Gefitinib Sensitivity of EGFR with Complex Mutations over Single Rare Mutation: Insights from Molecular Simulations

Abstract: Epidermal growth factor receptor (EGFR) is an intensively focused target for anti-tumor compounds used in non-small cell lung cancer (NSCLC) therapy. Compared to the classical activating mutations, there are still many uncommon EGFR mutations associated with poorer responses to EGFR inhibitors. A detailed understanding of the molecular basis for multiple EGFR mutants exhibiting diverse responses to inhibitors is of critical importance for related drug development. Herein, we explored the molecular determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…5a ). Helix αC changes that result from profile 2 exon 19 deletions between β3 and αC are presumably communicated to αE through these interactions, which interestingly were also recently implicated in differential gefitinib sensitivity in molecular dynamics studies 46 . The altered αE peptide also includes M825, the side chain of which contacts H835 in the conserved HRD motif at the beginning of the TKD’s catalytic loop—propagating αC changes to the catalytic loop.…”
Section: Resultsmentioning
confidence: 91%
“…5a ). Helix αC changes that result from profile 2 exon 19 deletions between β3 and αC are presumably communicated to αE through these interactions, which interestingly were also recently implicated in differential gefitinib sensitivity in molecular dynamics studies 46 . The altered αE peptide also includes M825, the side chain of which contacts H835 in the conserved HRD motif at the beginning of the TKD’s catalytic loop—propagating αC changes to the catalytic loop.…”
Section: Resultsmentioning
confidence: 91%
“…In the early stage, gefitinib was frequently administered to treat patients with L833V/H835L mutations, this preference may be attributed to previous findings that gefitinib exhibit activity in patients with compound EGFR-mutations (the response rate was 50%), albeit with lower efficacy compared to patients with common mutations ( Yu et al, 2018 ). Li et al also proved a more favorable response to gefitinib in patients with compound EGFR mutations compared to those with a single rare variant through molecular dynamics simulations assay ( Li et al, 2022 ). Among the 9 cases included in Table 1 , 4 patients were treated with the gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…used molecular dynamics simulations to thoroughly investigate the molecular basis of gefitinib sensitivity of EGFR compound variants and single rare variants. The results showed that EGFR compound variants were more sensitive to gefitinib than single rare variants [ 6 ]. In terms of clinical treatment data, some studies found that patients with compound variants had an ORR of 6.2%–16.7% in first-line EGFR-TKI therapy, much lower than patients with single or classical EGFR variants (62.1%–84.6%), leading to varying degrees of shortened PFS and overall survival (OS) [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%